Effective Communication Teamwork and Leadership with Soft Skills - Nan Zakiah Megat Ibrahim; Aida Zuliyana Ahmad Anuar; Aida Suhana Abd Hamid; Mohamad Shamsul Ibrahim, (Journal of Human Development and Communication (JoHDeC), 2025)
There are still very limited studies in proving effective communication, teamwork and leadership that can contribute toward one’s soft skills in the context of Malaysian students. This research also to study the relationship between effective communication, teamwork and leadership with soft skills of the teenagers in Kuala Lumpur. This study applied the Theory of Traits as the main theory to further strengthen the relationship between each variable. Quantitative methods were applied in this study and data were collected through the distribution of questionnaires to 250 respondents among teenagers in Kuala Lumpur. The findings showed a significant relationship between effective communication, teamwork, leadership and soft skills to participation students. Hence, this study contributes to the field of communication through the establishment of a more comprehensive variables related to soft skills.